2012
DOI: 10.5414/cn107167
|View full text |Cite
|
Sign up to set email alerts
|

Differences in community, hospital and intensive care unit-acquired acute kidney injury: observational study in a nephrology service of a developing country

Abstract: AKI is a frequent and frequently fatal condition. Mortality was higher in community and ICU-acquired than hospital ward-acquired AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…All of these were performed in patients with CA-AKI admitted to the hospital. Two of these studies, based in Brazil and China, had less than a third of the patient numbers presented here (27,28). The causes of AKI, as well as the prevalence of various comorbid conditions in these studies, probably differ from those present in our (22,23).…”
Section: Discussionmentioning
confidence: 90%
“…All of these were performed in patients with CA-AKI admitted to the hospital. Two of these studies, based in Brazil and China, had less than a third of the patient numbers presented here (27,28). The causes of AKI, as well as the prevalence of various comorbid conditions in these studies, probably differ from those present in our (22,23).…”
Section: Discussionmentioning
confidence: 90%
“…While technological advances enable treatments for many diseases, we continue to encounter traumatic rhabdomyolysis as a result of wars, terror attacks, earthquakes, and other natural disasters1617. Mesenchymal stem cells are one of the few stem cell types that have been applied as therapeutic agents for immunomodulation and tissue repair, which highlights their potential for recovery from kidney injury6.…”
Section: Discussionmentioning
confidence: 99%
“…The efforts of nephrology and critical care societies to create a unified classification system have enabled comparisons of AKI incidence and outcomes across diverse populations. The resultant epidemiological studies have shown increasing severity of AKI cases and a higher risk of death associated with AKI, in both hospital and community settings [10][11][12]. In addition, AKI is now a recognized important risk factor for new-onset chronic kidney disease (CKD), determining acceleration in the progression to end-stage renal disease [13][14][15].…”
Section: Introduction Of 0 By 25 Projectsmentioning
confidence: 99%